STUDIES ON THE EXCRETORY PRODUCTS OF PEBRINE INFECTED TASAR SILKWORM, ANTHERAEA MYLITTA DRURY (DABA TV) - G. RENUKA; G. SHAMITHA (International Journal of Pharma and Bio Sciences, 2012)
The tasar silkworm Antheraea mylitta Drury, is an important sericigenous insect reared outdoor and it is commercially exploited in 9 states of tropical India. , Pebrine is a disease caused in tasar silkworms, by a parasitic microsporidian- Nosema mylittensis leading to slow growth, undersized body and extreme crop loss. As excretion forms an important factor for the balance of nitrogen in the body, the present studies gives detail of the excretory products from fifth instar Pebrine-free and pebrine infected Tasar silkworm, Antheraea mylitta Drury (Daba TV)., The main excretory products like urea, uric acid, glutamine and ammonia were at a higher level in Pebrine-free worms as compared to Pebrine infected Tasar silkworms.